Last Interglacial (MIS5e) hydrographic shifts linked to meltwater discharges from the East Greenland margin. (15th May 2017) - Zhuravleva, Anastasia; Bauch, Henning A.; Van Nieuwenhove, Nicolas
Abstract: Proximal evidence of the surface ocean response to size reduction of the Greenland Ice Sheet (GIS) during the Last Interglacial (MIS5e) and preceding glacial termination (T2) remains largely elusive. Using a new sediment record from the western Iceland Sea, the behavior of the northeastern GIS and its relation to the subpolar North Atlantic surface hydrography is examined. Extremely light oxygen isotopic (δ 18 O) values are found off central East Greenland during early MIS5e and point to enhanced meltwater release, potentially from the northeastern sector of the GIS. Data from downstream the cold East Greenland Current (EGC) and its eastward branches suggest a far-reaching effect of this meltwater not only in the Nordic Seas but also in the SE Labrador Sea. In particular, whereas an early MIS5e warming (at ∼128.5–126.5 ka) in the two regions coincided with the relative reduction of meltwater input into the EGC, the subsequent cooling noted at ∼126.5 ka followed a renewed major freshwater event off central East Greenland. Our data further indicate persistent freshwater influence from the East Greenland margin over the entire MIS5e interval and, in addition, also reveal a late MIS5e meltwater event. The latter event occurred just prior to the last glacial inception and emphasizes the importance of Greenland meltwater as forcing factor on Interglacial climates. Highlights: Pronounced northeastern Greenland Ice Sheet retreat during early MIS5e. Downstream effect of Greenland-derived meltwater. Climatic decoupling between the Nordic Seas, the North Atlantic and the Labrador Sea. Meltwater event during late MIS5e.